An approach to design extrusion dies for complex shaped rubber profiles using finite element analysis. (September 2020) - Sharma, Sujit; Sarkar, Kajal; Goswami, Mohit; Deb, Arghya; Dcunha, Stany; Chattopadhyay, Santanu
Graphical abstract: Abstract: Extrusion is one of the most useful processes for making long rubber product profiles. The profile deforms while extruding due to swelling based on the geometry of the die, thermal and rheological properties of the material, and predominantly on the thermal and rheological boundary conditions. In this work, it is attempted to develop a possible strategy for simulating the flow and predicted the required die design to obtain the desired extrudate shape by using the proper rheological parameters and boundary conditions. Constitutive rheological models are fitted with experimental data to acquire material constants. Here, finite element analysis (FEA) of direct and inverse extrusion is performed to assess the swelling behavior of the product. The efficacy of the direct and inverse simulation is investigated for the overall deformation of the final products. The deformation is found to be a minimum (4 %) when inverse extrusion simulation is used in comparison with direct extrusion simulation (13 %). The outcome of FEA is validated with the experimental result and found a correlation coefficient of 0.986.